Uji Konsentrasi Zat Kapur (CaCO3) Pada Air Sumur Di Desa Rarang Selatan Kecamatan Terara Kabupaten Lombok Timur - Nurdin Nurdin; Lalu Ragil Qiansantang; Pahmi Husain; Baiq Naili Dewi Atika; Dwi Kartika Risfianty; irma Risvana Dewi (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2022)
Water is a means of improving the health status of the community, its quality needs to be maintained so that it is still beneficial for human life and other living things and water control is still carried out. Improving the quality of drinking water by managing it is absolutely necessary, especially if the water comes from surface water. South Rarang Village is deemed necessary to conduct research on the concentration of lime (CaCO3) in well water in South Rarang Village because it is seen that when the community boils water taken from the well, scale develops in the water heating boilers. The sample in this study was part of the wells of the people of South Rarang Village, Terara District, East Lombok Regency. The sampling criteria used by the researchers in this study were based on the location and location of the wells in each hamlet in Rarang Selatan Village, Terara District, East Lombok Regency. Based on the results of testing well water in Rarang Selatan Village, Terara District, East Lombok Regency at the Lombok Island Public Health Laboratory, it can be concluded that the average lime content in each well in South Rarang Village has an average of 432 mg/liter